PENERAPAN KONSELING KELOMPOK BERBASIS CBT UNTUK MENGURANGI PERILAKU MEMBOLOS SISWA DI MTSN 3 SURABAYA - Cahaya Ratih (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2025)
This study aims to analyze strategies for handling students who frequently truant at MTsN 3 Kota Surabaya through a group counseling approach based on Cognitive Behavior Therapy (CBT). This study was conducted using a descriptive qualitative method using observation, interviews, documentation, and content analysis techniques. The results showed that internal factors such as lack of motivation, discomfort with the school environment, and external factors such as lack of parental attention were the main triggers of truancy behavior. The CBT approach was implemented through self-instruction techniques, where students were guided to identify negative thoughts, build positive self-talk, and develop adaptive strategies in dealing with situations that trigger truancy. Group counseling played an important role in increasing students' self-confidence, self-efficacy, and social skills. Psychosocial support was also found to be an important component in helping them adapt to new positive habits. The results showed that the combination of self-instruction techniques and psychosocial support was effective in reducing truancy behavior and increasing student participation in school.